Career specialty choices of UK medical graduates of 2015 compared with earlier cohorts: questionnaire surveys - Lambert, T; Smith, F; Goldacre, M (BMJ Publishing Group, 2018)
Objective To report the career specialty choices of UK medical graduates of 2015 one year after graduation and to compare these with the choices made at the same postgraduate stage by previous cohorts. Design National survey using online and postal questionnaires. Setting UK. Participants UK-trained medical graduates. Main outcome measures Grouped and individual specialty choices. Results The response rate was 41.3% (3040/7095). Among the graduates of 2015, general practice (27.8% of first choices) and hospital medical specialties (26.5%) were the most frequent first choices of long-term career. First choices for general practice declined among women from 36.1% for the 2005–2009 cohorts to 33.3% for the 2015 cohort, and among men from 22.4% for the 2005–2009 cohorts to 19.3% for the 2015 cohort. First choices for surgery declined among men (from 29.5% for the 2005–2009 cohorts to 21.7% for the 2015 cohort), but not among women (12.3% for the 2005–2009 cohorts and 12.5% for the 2015 cohort). There was an increase in the percentage of first choices for anaesthesia, psychiatry, radiology and careers outside medicine. Anaesthesia, oncology, paediatrics and radiology increased in popularity over time among men, but not among women. Conclusions Career choices for general practice remain low. Other current shortage specialties, apart from radiology and psychiatry, are not showing an increase in the number of doctors who choose them. Large gender differences remain in the choices for some specialties. Further work is needed into the determinants of junior doctors’ choices for shortage specialties and those with large gender imbalances.